Knowledge Management from Bananas for Utilization and Transfer of Knowledge to Communities : Case Study of Farmer’s Group Nong Yai Phim, Nang Rong District, Buriram Province - ละเอียดอ่อน ครุปกรณ์ (Community and Social Development Journal, 2018)
This research is participatory action research (PAR). In the space for storage. interview The meeting was to exchange knowledge and discussion groups for the data were analyzed through SWOT community. Then analysis the knowledge about the production of banana farmers in Nong Yai Pim. Consisting of banana cultivation, Breed, A separate dig Bud, Irrigation of banana tree, Trimming banana suckers, the cut banana leaves ,the support banana , banana harvest and sales channels. Meanwhile, a group of farmers had gathered. To study the banana processing enterprises. Ban Don Somboon Non Suwan District Buriram province. Then come back together for a brief meeting. Bananas can find many processed. And the farmers agreed to privatize the banana banana to find the right ratio. Then measure the satisfaction level of service. Found that the participants were satisfied with the knowledge or the highest 4.25 Followed by the process or the service provider and the authorities equal to 4.23 and 4.17 respectively.